2018
DOI: 10.1021/acs.jafc.8b00369
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography/Mass Spectrometry-Based Metabolite Profiling of Nutrients and Antinutrients in Eight Lens and Lupinus Seeds (Fabaceae)

Abstract: Lens culinaris and several Lupinus species are two legumes regarded as potential protein resources aside from their richness in phytochemicals. Consequently, characterization of their metabolite composition seems warranted to be considered as a sustainable commercial functional food. This study presents a discriminatory holistic approach for metabolite profiling in accessions of four lentil cultivars and four Lupinus species via gas chromatography/mass spectrometry. A total of 107 metabolites were identified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Pyruvic acid ( 2 ) a ketocarboxylic acid was found more in grilled corn due to thermal degradation of furan molecules (De Rovira, ). It should be noted that the absence of phytic acid, an antinutrient forming chelates with mineral and protein decreasing their bioavailability, in investigated corn variety suggest its good quality (Farag, Khattab, et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Pyruvic acid ( 2 ) a ketocarboxylic acid was found more in grilled corn due to thermal degradation of furan molecules (De Rovira, ). It should be noted that the absence of phytic acid, an antinutrient forming chelates with mineral and protein decreasing their bioavailability, in investigated corn variety suggest its good quality (Farag, Khattab, et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of primary metabolites followed the exact protocol detailed in our previous work [24,[70][71][72]. 100 µL of 50% aqueous extract (prepared by extracting 100 mg of fruit skin and pulp in 5 mL 50% MeOH) was evaporated under nitrogen till dryness.…”
Section: Gc-ms Analysis Of Silylated Primary Metabolitesmentioning
confidence: 99%
“…The bioactive compounds are formed by secondary plant metabolism and may cause different pathologies (Wink 1992). In a recent study, Farag et al (2018) identified 107 metabolites from different species of Lupinus, comprising organic compounds, sugars, and sterols. However, different approaches must be carried out to explore other factors related to the composition such as collection site, seasonal variation, and extraction conditions.…”
Section: Lupinus Sp Genusmentioning
confidence: 99%